2008
DOI: 10.1523/jneurosci.3962-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Mutant Form of the Ferritin Light Chain Gene Induces Neurodegeneration and Iron Overload in Transgenic Mice

Abstract: Increased iron levels and iron-mediated oxidative stress play an important role in the pathogenesis of many neurodegenerative diseases. The finding that mutations in the ferritin light polypeptide (FTL) gene cause a neurodegenerative disease known as neuroferritinopathy or hereditary ferritinopathy (HF) provided a direct connection between abnormal brain iron storage and neurodegeneration. HF is characterized by a severe movement disorder and by the presence of nuclear and cytoplasmic ferritin inclusion bodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
119
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(132 citation statements)
references
References 30 publications
11
119
2
Order By: Relevance
“…We observed that ferritin precipitates obtained in vitro were composed of fully assembled 24-mers, similar to what has been reported in inclusions in patients with HF (9, 12) and in transgenic mice expressing the MT-FTL polypeptide (29). At iron: ferritin ratios above 2000:1, under the same experimental conditions in which we analyzed WT-and MT-FTL, the majority of FTH1 but not WT-FTL ferritins precipitate (16).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We observed that ferritin precipitates obtained in vitro were composed of fully assembled 24-mers, similar to what has been reported in inclusions in patients with HF (9, 12) and in transgenic mice expressing the MT-FTL polypeptide (29). At iron: ferritin ratios above 2000:1, under the same experimental conditions in which we analyzed WT-and MT-FTL, the majority of FTH1 but not WT-FTL ferritins precipitate (16).…”
Section: Discussionsupporting
confidence: 87%
“…In this mouse model, the human MT-FTL polypeptide forms heteropolymers with the endogenous murine wild type Ftl and Fth1 polypeptides, which are seen to aggregate in neurons and glia throughout the life span of the mice (29). After treatment of the cells with FAC to increase their intracellular iron stores, we observed a switch of ferritin from the detergentsoluble fraction to the detergent-insoluble fraction, suggesting a change in the solubility (Fig.…”
Section: Chelation Of Iron Reverses Iron-induced Aggregation In Vivo-mentioning
confidence: 78%
See 1 more Smart Citation
“…The common property of the two mutants is a major conformational alteration of the C terminus, which was exposed to solvent and accessible to proteolytic enzymes. Moreover, the expression of human L167fs in transgenic mice was shown to cause a phenotype with cytosolic and intranuclear ferritin aggregates analogous to those found in the patients (27), and to cause a deregulation of brain iron with up-regulation of the endogenous ferritin, down-regulation of transferrin receptor, and reduced RNA binding activity of IRP1 (26).…”
mentioning
confidence: 81%
“…In contrast, the mutant L167fs was shown to be as soluble as L-wild type (Lwt), to be less thermostable, and to form aggregates when incubated with an excess of Fe(II) in aerobic conditions (22,24,25). It was proposed that these iron-rich ferritin aggregates contribute to the formation of ferritin bodies in vivo and alter ferritin functionality (26,27). Studies on cellular models showed that the expression of L154fs and L167fs caused remarkably similar phenotypes, with the accumulation of endogenous ferritins, an increase of labile iron pool and oxidative damage, joined to a reduction of ferritin half-life and proteasome activity (22).…”
mentioning
confidence: 99%